In vitro activity of antibiotics potentially effective against difficult-to-treat strains of Gram-negative rods: retrospective study - Kroneislová, Gabriela; Závora, Jan; Adámková, Vanda Gabriela; Rýdlová, Anna; Adámková, Václava (Scientific reports, 2024)
Bacterial resistance surveillance is one of the main outputs of microbiological laboratories and its results are important part of antimicrobial stewardship (AMS). In this study, the susceptibility of specific bacteria to selected antimicrobial agents was tested. The susceptibility of 90 unique isolates of pathogens of critical priority obtained from clinically valid samples of ICU patients in 2017-2021 was tested. 50% of these fulfilled difficult-to-treat resistance (DTR) criteria and 50% were susceptible to all antibiotics included in the definition. 10 Enterobacterales strains met DTR criteria, and 2 (20%) were resistant to colistin (COL), 2 (20%) to cefiderocol (FCR), 7 (70%) to imipenem/cilastatin/relebactam (I/R), 3 (30%) to ceftazidime/avibactam (CAT) and 5 (50%) to fosfomycin (FOS). For Enterobacterales we also tested aztreonam/avibactam (AZA) for which there are no breakpoints yet. The highest MIC of AZA observed was 1 mg/l, MIC range in the susceptible cohort was 0.032-0.064 mg/l and in the DTR cohort (incl. class B beta-lactamase producers) it was 0.064-1 mg/l. Two (13.3%) isolates of Pseudomonas aeruginosa (15 DTR strains) were resistant to COL, 1 (6.7%) to FCR, 13 (86.7%) to I/R, 5 (33.3%) to CAT, and 5 (33.3%) to ceftolozane/tazobactam. All isolates of Acinetobacter baumannii with DTR were susceptible to COL and FCR, and at the same time resistant to I/R and ampicillin/sulbactam. New antimicrobial agents are not 100% effective against DTR. Therefore, it is necessary to perform susceptibility testing of these antibiotics, use the data for surveillance (including local surveillance) and conform to AMS standards.
Keywords: Anti-Bacterial Agents; Gram-Negative Bacteria; Aztreonam; Cefiderocol; azabicyklické sloučeniny; Retrospective Studies; Colistin; Azabicyclo Compounds; Microbial Sensitivity Tests; gramnegativní bakterie; Pseudomonas aeruginosa; retrospektivní studie; Humans; cefalosporiny; aztreonam; antibakteriální látky; Cephalosporins; cefiderokol; mikrobiální testy citlivosti; lidé; kolistin